If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(-4) = 4x + 6 Multiply -1 * -4 2x + 4 = 4x + 6 Reorder the terms: 4 + 2x = 4x + 6 Reorder the terms: 4 + 2x = 6 + 4x Solving 4 + 2x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + 2x + -4x = 6 + 4x + -4x Combine like terms: 2x + -4x = -2x 4 + -2x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + -2x = 6 + 0 4 + -2x = 6 Add '-4' to each side of the equation. 4 + -4 + -2x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = 6 + -4 -2x = 6 + -4 Combine like terms: 6 + -4 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 1x-5y=10 | | 8+3x-6x=-10 | | x+4y=500 | | 12a-9b=6 | | (2x-4)=4x+6 | | 5x-15+6=5x-10 | | -0.1x-11=89 | | 6+y+x=24 | | 3s-9t=15 | | 6x-33=9(x+1) | | b/2+5=20 | | 8x+3y=-46 | | 2x^2+8x+16=15 | | P=15-.75n | | -7u=49 | | m+-4=9 | | 11z=8z-6 | | 2(16+x)=8(3+1) | | (-5)+(-3)= | | -x+10-x=0 | | -5h-6=12 | | 4y^2+13y+10=0 | | -5k=25 | | (4x-10)+2x=38 | | -5x+8=2x+9-7x | | 7(2x+3)=4x-9 | | 6(3+x)=4(6+8) | | 4v-1=-8v | | 27-11z=z-33 | | 8x+3-10x=-2x-4+3 | | y=-25(25)+1050 | | 2u+1=u+10 |